Calculation of distribution functions and diffusion coefﬁcients for ions in the system “initial electrolyte solution – membrane” - Zhelem, R.I.; Tokarchuk, M.V.; Omelyan, I.P.; Sovyak, E.M. (Condensed Matter Physics, 1999)
Diffusion of ions under inhomogeneous conditions in the two-phase system “initial electrolyte solution-membrane” is investigated. Expressions for the friction constant, self- and interdiffusion coefﬁcients are derived by means of a nonequilibrium statistical operator for an inhomogeneous case. They are applied to the system, thus the behaviour of the position-dependent selfdiffusion coefﬁcient for NaCl near a reverse osmosis membrane is evaluated.